ON THE BINARY DIGITS OF ALGEBRAIC NUMBERS - KANEKO, HAJIME (Journal of the Australian Mathematical Society (2001), 2010)
Borel conjectured that all algebraic irrational numbers are normal in base 2. However, very little is known about this problem. We improve the lower bounds for the number of digit changes in the binary expansions of algebraic irrational numbers.